Fulfillment of The Civil Rights of Prisoners Concerning Legal Cases Relating To Divorce - Agustini, Shenti (Faculty of Law, Universitas Pattimura, 2022)
Introduction: One type of human rights is civil rights. Correctional institutions are places to build relationships with civil rights concerns. However, in practice, when dealing with divorce cases, they cannot attend the divorce party and are not given a verstek decision. Purposes of the Research: The purpose of this study is to analyze the implementation of Law No. 12 of 1995 concerning Corrections.Methods of the Research: The research method is normative juridical. This study also uses a juridical basis and a theoretical basis. The juridical basis used is 1945 Constitution, Law Number 1 of 1974 concerning marriage, Law Number 12 of 1995 concerning Corrections and the theoretical basis used is theory of legal objectives according to Gustav Radbruch.Results of the Research: Based on the results of the study, the law on corrections has not yet achieved its legal objectives. This is due to the weak structure, substance and culture of prisons. This causes whether or not the civil rights are fulfilled. Therefore, it is necessary to revise the correctional law by taking into account civil rights when dealing with divorce cases.